Cakelicious: Web App for Designing a Customised Wedding Cakes - Muhaini Othman; Mohd Shuqor Nordin; Mohd Hafizul Afifi Abdullah; Munirah Mohd Yusof; Rozlini Mohamed (Politeknik Negeri Padang, 2017)
In the fast-paced changing world, the Internet keeps people connected to each other. Online shopping has changed the way people buy things, and so does how people book flight tickets and movie passes. Cakelicious Web App is another interesting story of how we revolutionize the way people book wedding cakes the way they love it. The system is designed to replace the current manual booking methods used by Dr. Munie’s Kitchen for managing cakes order, thus is more efficient and effective, as well as meets the user requirements. Prototyping methodology approach has been used to develop and test the system in a systematic manner, which includes the development phases of planning, design, and testing and implementation. This system is developed using the PHP programming language, MySQL database, and runs on an Apache web server.